KARAKTERISTIK FLAME PROPAGATION PEMBAKARAN MESO SCALE COMBUSTOR DENGAN KOMBINASI SUDDEN EXPANSION DAN PLATE SEBAGAI FLAME HOLDER - Ahmad Syaihuddin Hasim (STATOR: Jurnal Ilmiah Teknik Mesin, 2022)
Currently, the development of various electronic devices withsizes is portable increasing rapidly, this causes the need for energy sources with compact sizes with high density to be increasingly needed. An example of an energy source with size portable is a battery. Batteries are needed as a source of power in various electronic technologies, but when examined further the battery has many shortcomings that have not been covered until now. Batteries have a relatively low energy density, besides that they also require handling of their hazardous waste. These various factors have prompted various studies to be carried out to find a new energy source that is more dense and efficient, namely the Micro Power Generator (MPG). This research was conducted with experimental where meso scale combustor with sudden expansion added a flame holder in the form of a plate which is controlled by varying diameter outlet on the combustor. Of the two variations in the diameter outlet, namely 8 mm and 10 mm, the results show that at conditions of equivalent ratio (Ф) = 1, the combustor 10 mm has a better flammability limit, more stable fire, and shape of the fire tends to wide. Combustor 10 mm with an average reactant velocity of 0,1039 m/s resulted in an average flame propagation velocity of 0,0889 m/s and combustor 8 mm with an average reactant velocity of 0,1623 m/s resulted in an average flame propagation velocity of 0,1385 m/s, from these results indicate that the higher the value reactant velocity than the faster the value flame propagation.